Urgensi Literasi Digital dalam Menangkal Radikalisme pada Generasi Millenial di Era Revolusi Industri 4.0 - Bastian, Oni Arizal; Rahmat, Hayatul Khairul; Basri, A Said Hasan; Rajab, Deni Dadang Ahmad; Nurjannah, N (Jurnal Dinamika Sosial Budaya, 2021)
In the era of the Industrial Revolution 4.0, which was marked by the massive development of information technology and the easy distribution of information without any filters. This study aims to explained the urgency of digital literacy in order to ward off radicalism in the millennial generation in the era of the Industrial Revolution 4.0. The method used in this research is literature review with content analysis techniques. The conclusion of this study is that digital literacy skills are very important in warding off radicalism and need to be developed in eight essential elements, namely cultural, cognitive, constructive, communicative, creative, critical, and civic. In addition, to improve digital literacy skills, Siberkreasi activities can be used. Hopefully, with the digital literacy skills of a digital user, namely the millennial generation, they can filter the information obtained and ensure its correctness first.
Keywords: Digital Literacy; Internet; Millenial Generation; Radicalism; Information Technology